Сlarification of the state diagram of “Metal 1-Metal 2” systems by analyzing the “cloud” of data of combustion parameters of “Metal 1-Metal 2-Nitrogen” SHS systems - O.A. Шкода (Қарағанды университетінің хабаршысы. Физика сериясы)
The combustion of the “Metal 1 — Metal 2 — Nitrogen” systems in the layer-by-layer mode of self- propagating high-temperature synthesis was studied. A large amount of experimental data was obtained by changing the initial synthesis parameters. As a result, a “cloud” of data was obtained, and not a single curve. Since self-consistency of many factors that ensure the propagation of the combustion wave occurs in this sys- tem, the structure of the “cloud” of data obeys strict laws characteristic of dissipative structures of nonequilibrium nonlinear systems. Variations in the initial data made it possible to obtain changes in the combustion parameters in a wide range. The combustion parameters reflect the properties of the solid-liquid medium that is formed in the chemical reaction zone in the combustion wave. The combustion temperature is between the “liquidus” and “solidus” temperatures of the corresponding “Metal 1-Metal 2” binary phase dia- grams, where titanium, molybdenum, tungsten, and aluminum were used as the Metal. The resulting data “clouds” were compared with the corresponding phase diagrams of state.